Types of Semiotic Similitude in Dramatic Discourse: Transformation of a Play into a Theatrical Performance - Loginova, E.G. (Vestnik Rossijskogo universiteta družby narodov. Seriâ: Teoriâ âzyka, semiotika, semantika (Online), 2017)
The article is aimed at presenting types of semiotic similitude of the communicatively related semiotic acts in heterogeneous discursive space, namely dramatic discourse which includes monomodal discourse (play) and polymodal discourse (theatrical performance). Making an attempt to reveal the functional basis for intrasemiotic and intersemiotic code metamorphoses within the semiosphere of dramatic discourse the author pays special attention to analogy as a cognitive universal which ensures orderliness across modalities and thus accounts for integrational and complementary nature of communication. Model construction is chosen as a method of analyzing the characteristics and directions of semiosis in dramatic discourse. It makes it possible to define two types of semiotic similitude in dramatic discourse (semiotic identity and image) and to single out four interdependent vectors seen as a model which brings about orderliness through analogy when we deal with heterogeneous discursive space.